Language as identity in Vladimir Nabokov’s "Pale Fire" - Soghomonyan, Amalya (Bulletin of Yerevan University B: Philology, 2024)
Russia and the Russian language did not leave Nabokov throughout his life. The Russian language is an integral part of his identity as a writer. However, many agree that Nabokov "rejected the premise of linguistic determinism that our language defines our world" and asserted that "we think outside of any language". In one of the interviews, Nabokov commented on the topic of language: "I do not think in any language. I think in images." Each letter of the alphabet has a specific colour and hue, as well as the components that help to create images in the mind. This phenomenon echoes the ideas of French symbolism, particularly Charles Baudelaire's poetics of synaesthesia. This connection between language and imagination is a key concept in Nabokov's work that helps us re-evaluate the troubled moments in the lives of Nabokov's characters before they embark on a journey where they must get to the past to make sense of the present.
Keywords: Nabokov; Kinbote; Zemblan language; identity; Zembla; John Shade; broken English; BIC language; retranslation; Shakespeare; Timon of Athens